Comparison of chest radiograph reading methods for assessing progress of pneumoconiosis over 10 years in Wittenoom crocidolite workers. Issue 2 (February 1990) - de Klerk, N H; Musk, A W; James, A; Glancy, J J; Cookson, W O
Abstract : Thirty three pairs of chest radiographs taken up to 10 years apart were obtained for 33 subjects suffering from asbestosis who had applied for compensation to the Pneumoconiosis Medical Board of Western Australia. Multiple films from the period before the first radiograph in each pair, from the intervening period between the two, and from the period subsequent to the second radiograph were also available and all films were read by two independent readers according to the 1980 ILO classification of pneumoconiosis. Films were read twice as side by side pairs ten years apart, twice as two separate randomly ordered films ten years apart, and once as part of the full series of all available chest radiographs on each subject to assess which method provided the best consistency (between reader variation) and repeatability (within reader variation). Judging by consistency, the full series method performed as well as either of the other methods when assessing radiographic changes and significantly better when assessing the level of profusion of small opacities. There was little to choose between the other two methods either judging by consistency or repeatability, which could not be estimated for the full series method. Use of all available films for a subject is recommended for assessing single films, as in a prevalence study, as well as for documenting change in a longitudinal study.